Caffeine Adsorption onto Bentonite Clay in Suspension and Immobilized - Giane Gonçalves Lenzi; Maria Eduarda Kounaris Fuziki; Michel Zampieri Fidelis; Yuri Barros Fávaro; Mauricio Aparecido Ribeiro; Eduardo Sidinei Chaves; Ervin Kaminski Lenzi (Brazilian Archives of Biology and Technology, 2020)
Abstract This study describes the use of bentonite in suspension for the caffeine adsorption (pollutant of emerging concern) by taking different conditions of the pH, adsorbent mass, adsorbent calcination temperature and interferents into account. The results were compared with those obtained using bentonite immobilized in alginate beads. The acid medium has a greater efficiency for the caffeine adsorption and the adsorbent calcination temperature exerts, due to structural changes. Caffeine removal higher than 90% was obtained at optimized conditions. The Langmuir model indicated a better fit of the data and the adsorption capacity of caffeine onto bentonite. The bentonite immobilized led to a slower adsorption process in relation to the suspended.